Investigation student's attitude and intention to use social software in higher institutions of learning in Malaysia - Shittu, Ahmed Tajudeen; Madarsha, Kamal Basha; Nik Abdul Rahman, Nik Suryani; Tunku Ahmad, Tunku Badariah (2011)
Purpose – Social software usage is growing at an exponential rate among the present generation of students. Yet, there is paucity of empirical study to understand the determinant of its use in the present setting of this study. This study, therefore, seeks to investigate factors that predict students' attitudes and intentions to use this internet-base software.